HOW PRIOR KNOWLEDGE, PROSPECT, AND LEARNING BEHAVIOUR DETERMINE LEARNING OUTCOMES OF BIPA STUDENTS? - Imam Suyitno; Yuni Pratiwi; Roekhan Roekhan; Martutik Martutik (Jurnal Cakrawala Pendidikan, 2019)
Many learning theories explain that prior knowledge, prospects, and learning behavior affect student learning outcomes. Related with these theories, this study aimed to describe these three variables for graduate students and their correlation in learning in the BIPA elective program (Bahasa Indonesia untuk Penutur Asing/Indonesian Language for Native Speakers). In addition, this study also described the implications of these three variables on student learning outcomes. Therefore, this study used a quantitative approach involving 17 graduate students who choose BIPA specialization programs. Data about the prospects and learning behavior were collected using a questionnaire, while the student's prior knowledge data was collected using a test instrument that contained general knowledge about BIPA. Meanwhile, student learning outcomes were obtained from student achievement index modified to a standard score. Data analysis used multiple correlation techniques. The findings of the study indicate that the prior knowledge of students about BIPA is in a low category, their prospects and learning behavior are in the high category, and the achievement index shows that their learning outcomes are in the very high category. Student prior knowledge does not correlate with prospects and learning behavior, whereas student learning behavior correlates with their prospects. Simultaneously, the three variables do not correlate with their learning outcomes.